Peran E-Commerce dalam Meningkatkan Peluang bagi UMKM di Indonesia - Raaken Danendra A W; Silvana Purbawanti; Zella Fathona Aska (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The aim of this research is to find out how the role of e-commerce increases opportunities for MSMEs in Indonesia. The method used in this research is a qualitative approach with literature study as the main data source. We carried out the data collection process by searching literature with the keyword "The role of e-commerce in Indonesian MSMEs." on the Google Scholar platform. The results show that e-commerce has made a significant contribution to the MSME players themselves. The role of e-commerce has also increased since the COVID-19 pandemic, which at that time became the main solution for MSMEs to survive amidst the crisis caused by restrictions on physical activity. With e-commerce integrated with social media, MSMEs can still operate and maintain income because they are able to adapt to changes in market behavior. However, this research also identified several main challenges, one of which is the low interest in reading which causes a lack of digital literacy among MSME players. Therefore, technology training, digital infrastructure development, and policies that support the empowerment of MSMEs in the digital era are needed. By conducting this research, of course there is hope that strategic steps can be formulated to maximize the potential of e-commerce, not only in expanding market access on a global scale, but also being able to increase the global competitiveness of MSMEs in a sustainable manner.